Keteladanan Guru Sebagai Sarana Penerapan Pendidikan Karakter Siswa - Arfaiza, Shafina Alya; Susanti, Revina; Fitriani, Widya Ningrum; Caturiasari, Jennyta; Wahyudin, Dede (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
Character education is a learning process that provides support for the social-emotional and ethical development of students and an effort to build character. Character education aims to form a person who is devoted and faithful and who is more responsible for all behaviors possessed by students, such as self-confidence, innovation, passion, competitiveness, creativity, honesty, high social spirit, and kindness. With The application of character education in every aspect of learning is expected to support the creation of a more moral education. This article is the result of an analysis using the literature study method, or literature review. The results of the study show that exemplary teachers are continuously needed in efforts and struggles to instill noble values in strengthening student character, both in aspects of behavior, attitudes, and habits in the school environment and in other environments. The success of character education in schools depends entirely on how teachers conduct lessons. A teacher is a role model; a teacher is the pinnacle of everything. What a teacher does affects the development of students.